Risks from Ebolavirus Discharge from Hospitals to Sewer Workers - Haas, Charles N (Water environment research : a research publication of the Water Environment Federation, 2017)
Current World Health Organization and Centers for Disease Control and Prevention guidance for the disposal of liquid waste from patients undergoing treatment for Ebola virus disease at hospitals in the U.S. is to manage patient excreta as ordinary wastewater without pretreatment. The potential for Ebolavirus transmission via liquid waste discharged into the wastewater environment is currently unknown, however. Possible worker inhalation exposure to Ebolavirus-contaminated aerosols in the sewer continues to be a concern within the wastewater treatment community. In this study, a quantitative microbial risk assessment was carried out to assess a sewer worker's potential risk of developing Ebola virus disease from inhalation exposure when performing standard occupational activities in a sewer line serving a hospital receiving Ebola patients where there is no pretreatment of the waste prior to discharge. Risk projections were estimated for four scenarios that considered the infectivity of viral particles and the degree of worker compliance with personal protective equipment guidelines. Under the least-favorable scenario, the median potential risk of developing Ebola virus disease from inhalation exposure to Ebolavirus-contaminated aerosols in the sewer is approximately 10-5.77 (with a first to third quartile range of 10-7.06 to 10-4.65), a value higher than many risk managers may be willing to accept. Although further data gathering efforts are necessary to improve the precision of the risk projections presented here, the results suggest that the potential risk that sewer workers face when operating in a wastewater collection system downstream from a hospital receiving Ebola patients warrants further attention, and that current authoritative guidance for Ebolavirus liquid waste disposal-to dispose in the sanitary sewer without further treatment-may be insufficiently protective of sewer worker safety